Design And Development Of Programming Learning Platform Based On Heuristic Approach In Course Management Module With Iterative And Incremental Method (case Study : Information System Telkom University) - Alima Indriati; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract — Programming algorithm is one of course that must be taken by computer science’ students. In fact, Computer science’ student of computer science forced to familiar with programming skill. Not only student as novice programmer but also, programming algorithm is not just a single programming skills, but involve more than one different processes. LMS is one of e-learning technology that facilitate lecturer to managing course. It can use to help lecturer familiar with e-learning technology. The research aims to develop a heuristic learning Platform that called CIDEC PLATFORM focused in course management module. This platform can help lecturer to implement e-learning based on LMS technology. In this platform provide heuristic learning to find good solutions to an optimization problem. For platform develop, it will use iterative and incremental method made in four iteration by involving business modelling, requirement analysis, analysis and design, implementation, and testing. Platform based web application is built with by using concept Model-View-Template (MVT) which utilize Python programming language within Django Framework and MySQL database. The result of research is Programming Learning Platform. Index Terms— Course management module, CIDEC Platform, heuristic learning, iterative and incremental method